Outcome-Based Education in Higher Education Curricula: A Systematic Literature Review of Implementation Strategies and Implications for Biology Education - Necta Ayu Cahyanti; Slamet Suyanto; Kartika Ratna Pertiwi; Ngade Wantara; Nucleo Wildan Aprianto (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
The rapidly evolving paradigm of higher education necessitates curricula that are contextually relevant, empirically measurable, and rigorously outcome-oriented. Outcome-Based Education (OBE) responds to this imperative by systematically prioritizing learning outcomes as the foundational basis for curriculum design, instructional delivery, and student assessment. This study aims to examine the underlying principles, implementation strategies, and prevailing challenges of OBE in higher education, while further exploring its specific implications for biology education. A Systematic Literature Review (SLR) was conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. An initial corpus of 50 articles was retrieved from Google Scholar, Scopus, and Web of Science databases, of which 10 peer-reviewed articles published between 2023 and 2025 satisfied the predefined inclusion criteria and were subsequently subjected to thematic analysis. The findings indicate that OBE implementation is characterized by a strong emphasis on student-centered learning, predominantly supported by active pedagogical approaches including problem-based and project-based learning. Principal challenges encompass inadequate institutional resources, organizational resistance to curricular reform, and insufficient faculty professional development, whereas identified opportunities include demonstrable improvements in graduate competency and the adoption of outcomes-aligned assessment frameworks. Within the context of biology education, OBE demonstrably fosters integrative and contextual learning experiences that are well-aligned with the demands of 21st-century scientific competencies. Collectively, these findings affirm the substantial potential of OBE to meaningfully enhance the quality of higher education, while underscoring that its sustained effectiveness is contingent upon institutional readiness, stakeholder commitment, and fidelity of implementation.